Baby signing time! Vol. 2, Here I go [videorecording (DVD)]. (Two Little Hands Productions, 2007)
Children can learn the signs for shoe, sock, bike, Thank You, Sorry, and more as they learn how to communicate before even learning how to speak. Uses singing, dancing, speaking, and more.